Effects of Feed Restriction on Growth Performance, Nutrient Utilisation, Biochemical Parameters, and the Caecum Microbiota and Metabolites in Rabbits - Qi Lu; Jixiao Qin; Shuanglong Xie; Rui Chen; Xu Wang; Yiqing Xu; Yiming Ban; Chengcheng Gao; Peiyao Li; Di Zhou; Xingzhou Tian (Animals)
The main objective of this research was to observe the effects of feed restriction on caecum microbiota and metabolites in rabbits. Forty-eight male 8-week-old rabbits with similar body weights (1872.11 ± 180.85 g) were randomly assigned to two treatments according to completely randomized design: (1) the control group received ad libitum access to feed (AL), and (2) the treatment received 80% of the feed consumed by the control (FR). The results showed that FR did not differ (p > 0.05) for average daily weight gain or feed conversion ratio between the two groups. FR treatment led to a significant increase (p < 0.05) in acid detergent fibre apparent faecal digestibility, nitrogen digestibility and retention, and gross energy digestibility and retention. The FR treatment showed significantly (p < 0.05) lower blood triglycerides, creatinine, high-density lipoprotein cholesterol, malondialdehyde, and hydroxyl free radicals but significantly (p < 0.05) greater total antioxidant capacity and superoxide dismutase. The FR group presented greater (p < 0.05) Firmicutes and Ruminococcus abundances but a lower (p < 0.05) Akkermansiaceae abundance in the caecal content. Moreover, 222 differentiated metabolites were identified, and beta-alanine metabolism was the top enriched pathway. Collectively, FR can improve nutrient utilisation, lipid metabolism, antioxidant activity, caecum microbiota, and metabolites in rabbits.